PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP AKHLAK SISWA MTS ALWASHLIYAH PULAU GAMBAR KECAMATAN SERBAJADI KABUPATEN SERDANG BEDAGAI - Swita (Jurnal Bilqolam Pendidikan Islam, 2022)
This research is based on the seriousness of students in implementing Social Media both at home and at school which is seen from the Student Morals. Then the author's purpose of doing this research is to determine the effect of using social media on the morals of students in MTs Alwashliyah Pulau Gambar Subdistrict, Serdang Bedagai District, Serdang Bedagai Regency. The research that the author is doing here is a research using quantitative methods. After this research the author conducted at Mts Alwashliyah Pulau Gambar sub-district, Serdang Bedagai District, with a sample of 67 people and the data that the writer got was from students by using a questionnaire or questionnaire technique. As for the results of this study, social media showed the number 28.97. The results of the standard deviation of the variable x, namely Social Media, show a number of 0.9. And the highest frequency obtained from the variable x Social Media with a value of 30 gets a result of 15.41 % which can be said to be good .The result of the mean (average) of the y variable, namely Student Morals , shows a number of 3 0. The results of the standard deviation of the y variable, namely Student Morals , shows a number of 29.71. The standard deviation of the variable x, namely Student Morals , shows a number of 1.18. And the highest frequency obtained from the variable y, namely Student Morals with a value of 29 , got a result of 14.74 % which can be said to be lacking. After the writer conducted the research and got the mean (average) of the variable x and variable y as well as the highest frequency results from the variable x and variable y, the writer tested the hypothesis which got a result of 5.03